The Acquisition of Culturally Patterned Attention Styles Under Active Inference - Constant, Axel; Tschantz, Alexander Daniel Dunsmoir; Millidge, Beren; Criado-Boado, Felipe; Martinez, Luis M; Müeller, Johannes; Clark, Andy (Frontiers in Neurorobotics, 2021)
This paper presents an active inference based simulation study of visual foraging. The goal of the simulation is to show the effect of the acquisition of culturally patterned attention styles on cognitive task performance, under active inference. We show how cultural artifacts like antique vase decorations drive cognitive functions such as perception, action and learning, as well as task performance in a simple visual discrimination task. We thus describe a new active inference based research pipeline that future work may employ to inquire on deep guiding principles determining the manner in which material culture drives human thought, by building and rebuilding our patterns of attention.